Peningkatan Hasil Belajar Siswa Kelas VII Dengan Model Pembelajaran Missouri Mathematics Project (MMP) - Hasrul Kole; Christina Nely Laamena; Magy Gaspersz (LPPM Universitas Advent Indonesia, 2021)
Learning model Missouri Mathematics Project (MMP) is a structured learning to assist the teacher in an effectiveness of exercises use in groups or individuals for students to reach the improvement of learning result. Syntax learning of Missouri Mathematics Project (MMP) has five steps, namely: (1) introduction/review;(2)development;(3controlled exercise; (4)seatwork/independent work; and (5) Assignment or homework. This study was aimed to improve learning result of grade VII students of SMP Negeri 20 Ambon on equality and inequality materials of linear one variable using Missouri Mathematics Project (MMP) learning model. The Subjects of this study was grade VII students of SMP Negeri 20 Ambon consist of 24 students in academic year 2018-2019. The data of this study were qualitative and quantitative data. To measure the students’ learning level of grade VII students of SMP Negeri 20 Ambon, the analysis used is quantitative data analysis (Minimal Mastery Criteria) and qualitative data (Reduction, exposure and deduction). The result of this study showed that there are the improvement of students’ lerning result. It can be seen from the final test of cycle I to cycle II that the students who achieved minimal mastery criteria (MMC) were 13 students with a percentage 45,83%, meanwhile 13 students had not achieved minimal mastery criteria (MMC) with a percentage 54,17%. Thus, in cycle II, 19 students had achieved minimal mastery criteria (MMC) with a percentage 79,17% and 5 students had not achieved minimal mastery criteria (MMC) with a percentage 20,83%. From the percentage accomplishment of cycle I and cycle II, it is obtained an improvement from cycle I to cycle II by 33,34%. Based on the result of study, it can be concluded that the students’ learning result on the equality and inequality materials of linear one variable can be improved by using Missouri Mathematics Project (MMP) learning model at the grade VII students of SMP Negeri 20 Ambon.